Đánh giá chất lượng phản hồi của các bên liên quan trong phát triển chương trình dạy học ở các cơ sở giáo dục và đào tạo nhóm ngành sức khỏe tại Việt Nam - Lê, Thái Hưng; Nguyễn, Việt Hưng (Tạp chí Giáo dục, 2025)
In the context of competency-based higher education increasingly emphasizing the importance of stakeholder feedback to improve training programs, this study was conducted to evaluate the quality of feedback from four groups: lecturers, learners, former learners, and employers involved in developing teaching programs at six educational institutions with a history of health-related training. The results indicated that feedback from lecturers was rated highest in completeness, timeliness, and reliability. Feedback from learners and former learners was valuable but limited in relevance and accessibility. Meanwhile, feedback from employers scored the lowest, especially in accessibility. Based on these findings, the study proposed establishing a two-way, stable, and transparent feedback system between the school and stakeholders; standardizing survey tools appropriate for each group; and enhancing the roles of lecturers and employers in the program improvement process. The findings provide a practical foundation for designing internal quality assurance policies suited to the context of competency-based higher education in Vietnam.